2014
DOI: 10.1128/aem.00936-14
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Functional Antibody by Using a Green Fluorescent Protein Frame as the Template

Abstract: Single-chain variable fragment (scFv) antibodies are widely used as diagnostic and therapeutic agents or biosensors for a majority of human disease. However, the limitations of the present scFv antibody in terms of stability, solubility, and affinity are challenging to produce by traditional antibody screening and expression formats. We describe here a feasible strategy for creating the green fluorescent protein (GFP)-based antibody. Complementarity-determining region 3 (CDR3), which retains the antigen bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Additionally, a method for rapid and effective high-affinity GFP-based antibody production corresponding to scFv was developed. It was demonstrated by inserting CDR3 into green fluorescence protein (GFP) loops for improved disease diagnosis and therapy (Wang et al, 2014b). Skp co-expressing scFv has high solubility and binding activity to antigen thermolabile hemolysin (TLH) (a pathogenic factor of Vibrio parahaemolyticus) and was developed by using pACYC-Duet-skp co-expression vector.…”
Section: Single-chain Variable Fragment (Scfv)mentioning
confidence: 99%
“…Additionally, a method for rapid and effective high-affinity GFP-based antibody production corresponding to scFv was developed. It was demonstrated by inserting CDR3 into green fluorescence protein (GFP) loops for improved disease diagnosis and therapy (Wang et al, 2014b). Skp co-expressing scFv has high solubility and binding activity to antigen thermolabile hemolysin (TLH) (a pathogenic factor of Vibrio parahaemolyticus) and was developed by using pACYC-Duet-skp co-expression vector.…”
Section: Single-chain Variable Fragment (Scfv)mentioning
confidence: 99%
“…Alanine scanning showed that the Gln 1 , Arg and Pro residues of the CDR3 loop have the most prominent effects on antigen binding, and lysine scanning showed that the current Lys residue of the loop has the best binding affinity (Wang et al, 2014). In our structure, the Arg, Pro and Lys residues mainly help to stabilize the CDR loop structure, while residue Gln 1 is in a dynamic state and may be involved in direct interactions with the antigen.…”
Section: Resultsmentioning
confidence: 68%
“…For pathogen detection, a fluorobody was developed by inserting the L-CDR3 (light-chain complementary-determining region 3) of a high-affinity scFv into loop 9 of GFP (residues 171-176) (Wang et al, 2014). This fluorobody retains its fluorescence properties and binding specificity for thermolabile haemolysin (TLH), a toxin from Vibrio parahaemolyticus, a food-borne Gram-negative halophilic bacterium that causes lethal food-borne diseases and poses a serious threat to human and animal health all over the world (Burdette et al, 2008;Bresee et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For the Hepatitis B core antigen, the amino acid 144 served as an insertion site for heterologous antigen fusion (29). GFP protein has a thermal stable structure that constituted by 11 β-strands and 3 α-helices and some of the loops between strands have been explored as insertion sites for heterologous protein for various purposes (18,19,30). Among those candidates, loop173 linking strand 8 and strand 9 was chosen because it has a high capacity for foreign peptide insertion (Fig 3A) (30).…”
Section: Crafting a Vaccine Carrier That Enables Heterologous Antigenmentioning
confidence: 99%
“…So it is conceivable that the protein sequences among fluorescent protein family members in the barrel shell are highly variable and fluorescent proteins possess desirable biophysical properties can be selected using directed evolution (11,(14)(15)(16)(17). The applications of fluorescent protein have been expanded into multiple areas beyond live imaging which includes serving as biological sensors (18,19), or detectors for protein-protein interaction or protein folding (20,21).…”
Section: Introductionmentioning
confidence: 99%